The Influence of Social Media Marketing on Brand Awareness, Brand Image, Customer Engagement, and Purchase Decision - Setiawan, Budi; Cahyani, Putri Dwi; Hutami, Lusia Tria Hatmanti; Maharani, Bernadetta Diansepti (Economics and Business Solutions Journal, 2024)
This study aims to analyze how Social Media Marketing (SMM) influences Brand Awareness, Brand Image, Customer Engagement, and Purchase Decision. Using Signal Processing and Information Processing theories, this research identifies gaps in the literature regarding the relationship between SMM, Brand Awareness, Brand Image, Customer Engagement, and Purchase Decision. This research employs a quantitative approach with a survey method to collect data from 105 respondents. The sampling technique used is purposive sampling, which means selecting samples based on specific criteria relevant to the research. The criteria used are consumers who have seen or interacted with SilverQueen's social media marketing content. The collected data was analyzed using Smart PLS (Partial Least Squares) to test the structural model and measurement model. This study shows that Social Media Marketing plays a crucial role in enhancing Brand Awareness, Brand Image, Customer Engagement, and Purchase Decision for SilverQueen chocolate. The findings underscore the importance of effective social media marketing strategies for achieving better business outcomes.